IT solutions in logistics of smart bike-sharing systems in urban transport = Rozwiązania informatyczne wspierające logistykę wypożyczalni rowerów publicznych w miastach - Cichosz, Marzenna (Zielona Góra: Faculty of Economics and Management Press)
In recent years, the public transport of Krakow, Rzeszow, Wroclaw, Poznan, Opole and Warsaw has expanded into the third generation bike-sharing programs - smart bikes. It's an innovative solution, deploying IT systems and technology to integrate individual stations of urban bike rental system. The article presents the business model solution, its functionality from the perspective of customers and operator, and shows the role of IT solutions support in managing the logistics of rental network. An illustrative case of "Veturilo" solution implementation is presented.
Keywords: rower publiczny; logistyka miejska; zrównoważony rozwój transportu miejskiego; transport miejski; Bike-sharing; public bike; urban logistics; sustainable urban transport